2016
DOI: 10.1039/c6nr03810g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen exchange reaction at the ohmic interface in Ta2O5-based ReRAM devices

Abstract: Interface reactions constitute essential aspects of the switching mechanism in redox-based resistive random access memory (ReRAM). For example, the modulation of the electronic barrier height at the Schottky interface is considered to be responsible for the toggling of the resistance states. On the other hand, the role of the ohmic interface in the resistive switching behavior is still ambigious. In this paper, the impact of different ohmic metal-electrode (M) materials, namely W, Ta, Ti, and Hf on the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
118
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 38 publications
11
118
1
2
Order By: Relevance
“…Contrary to the active ohmic electrodes of relatively high thickness [26], no scavenging effect is observed for the thin Zr layer inserted between the inert top Au electrode and oxide material. The comparison with the reference Au/oxide/TiN/Ti devices has shown that the presence of a thin adhesive Zr layer results in some changes of differential resistances and dielectric properties (decrease in dielectric losses) of the capacitors in the initial state.…”
Section: Methodsmentioning
confidence: 71%
“…Contrary to the active ohmic electrodes of relatively high thickness [26], no scavenging effect is observed for the thin Zr layer inserted between the inert top Au electrode and oxide material. The comparison with the reference Au/oxide/TiN/Ti devices has shown that the presence of a thin adhesive Zr layer results in some changes of differential resistances and dielectric properties (decrease in dielectric losses) of the capacitors in the initial state.…”
Section: Methodsmentioning
confidence: 71%
“…In this scope, yttria stabilized zirconia (YSZ) ZrO 2 (Y) is very promising for RRAM applications since the V O concentration in YSZ is equal to 1/2 that of Y, and can be controlled precisely by varying Y molar fraction [4]. Although a lot of work was devoted to studying RS, many details of the RS mechanism in oxides are not clarified completely yet [5], including the processes at the metal-dielectric interfaces, particularly, the electric-field induced transition of O 2− ions from the dielectric into the metal electrode and back [6]. For deeper understanding of the microscopic details of RS mechanism, the appropriate experimental techniques are needed.…”
Section: Introductionmentioning
confidence: 99%
“…10,[13][14][15][16][17] Current studies are discussing the possibility of oxygen transfer reactions between the oxide and the metal electrodes as additional effects involved in VCM-type resistive switching. [18][19][20] Due to its thoroughly investigated defect chemistry, strontium titanate (STO) is often used as a model system for resistive switching. 21,22 Recently, several studies have dealt with the influence of stoichiometry on resistive switching in STO, revealing differences in forming voltage and statistics, 23 data retention, 24 or even switching/no-switching.…”
Section: Introductionmentioning
confidence: 99%